2002
DOI: 10.1210/rp.57.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Mammalian Gamete Binding

Abstract: Despite the importance of fertilization for controlling human reproduction, regulating animal production, and promoting preservation of endangered species, the molecular basis underlying gamete binding and fertilization has been perplexing. More progress has been made in the mouse than in other mammals and, recently, targeted deletion of specific genes in the mouse has yielded intriguing results. This review will emphasize research performed by our laboratory and others done primarily with mouse gametes but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 144 publications
0
19
1
Order By: Relevance
“…Moreover, the presence of a-L-fucosidase on the plasma membrane over the acrosome rules out the possibility that also this glycosidase might be involved in the primary binding between sperm and egg, as hypothesized in D. melanogaster . The presence on the surface of Ceratitis sperm of several glycosidases that might interact with complementary glycoconjugates of the egg surface (manuscript in preparation) is not surprising, since several authors have hypothesized that more than one receptor is involved and that the spermeegg binding is regulated by the sum of several molecular interactions (Wassarman et al, 2001;Miller et al, 2002;Lyng and Shur, 2007). Future experiments will provide to determine whether also in C. capitata b-N-acetylhexosaminidase, a-L-fucosidase and a-mannosidase are involved in spermeegg interactions and this work represents a starting point to unravel the precise role played by these glycosidases in gamete recognition in the Tephritidae family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the presence of a-L-fucosidase on the plasma membrane over the acrosome rules out the possibility that also this glycosidase might be involved in the primary binding between sperm and egg, as hypothesized in D. melanogaster . The presence on the surface of Ceratitis sperm of several glycosidases that might interact with complementary glycoconjugates of the egg surface (manuscript in preparation) is not surprising, since several authors have hypothesized that more than one receptor is involved and that the spermeegg binding is regulated by the sum of several molecular interactions (Wassarman et al, 2001;Miller et al, 2002;Lyng and Shur, 2007). Future experiments will provide to determine whether also in C. capitata b-N-acetylhexosaminidase, a-L-fucosidase and a-mannosidase are involved in spermeegg interactions and this work represents a starting point to unravel the precise role played by these glycosidases in gamete recognition in the Tephritidae family.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that in the early gamete recognition glycosidases and glycosyltransferases are the first receptors for the egg surface both in vertebrates and in invertebrates (Hoshi et al, 1983(Hoshi et al, , 1985Hoshi, 1984;Tulsiani et al, 1997;Martinez et al, 2000;Mengerink and Vacquier, 2001;Koyanagi and Honegger, 2003;Zitta et al, 2006;Lyng and Shur, 2007). In particular, in mammals, it has been indicated that several other proteins of the sperm surface, such as proteases, tyrosine kinases, phospholipase, may also function as receptors for the egg zona pellucida (Mengerink and Vacquier, 2001;Wassarman et al, 2001;Miller et al, 2002;Talbot et al, 2003;Shur et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear yet which sugars are involved in this interaction, but in vitro studies have suggested that it is stereo specifi c, with the participation of polysulphated sugar residues (Jones, 1991;Lo Leggio et al, 1994). One is a terminal β-1,3 galactose (Bleil and Wassarman, 1988) and the other is a terminal N-acetylglucosamine proposed to bind β-1,4 galactosyl transferase, a putative sperm receptor (Miller and Ax, 1990;Miller et al, 2002). Furthermore, the continued fertility of mutant mice lacking either the enzyme that adds terminal β-1,3 galactose (Thall et al, 1995)or b-1,4 galactosyltransferase (Shi et al, 2001) makes it unlikely that these are the sole determinants of mouse sperm binding.…”
Section: Discussionmentioning
confidence: 99%
“…Gamete binding in many species has been proposed to involve interactions between proteins on sperm and glycoconjugates on the egg surface (Mengerink and Vacquier, 2001;Evans, 2012;Clark, 2013Clark, , 2014. In particular, experimental evidence suggest that sperm surface glycosidases could act in a non-catalytic or lectinlike manner, recognizing complementary sugar moieties in the egg envelope (Miranda et al, 2000;Martinez et al, 2000;Perotti et al, 2001;Miller et al, 2002;Intra et al, 2006;Zitta et al, 2006;Hedrick, 2008;Honegger and Koyanagi, 2008;Intra et al, 2011). Examples of glycosidases on the sperm plasma membrane include mannosidases and fucosidases in mammalian sperm (Tulsiani et al, 1989(Tulsiani et al, , 1990Venditti et al, 2010;Phopin et al, 2012Phopin et al, , 2013, fucosidases and N-acetylglucosaminidases in tunicates (Hoshi et al, 1983(Hoshi et al, , 1985(Hoshi et al, , 1994Hoshi, 1986;Godknecht and Honegger, 1991;Matsumoto et al, 2002;Downey and Lambert, 1994), and mannosidases, fucosidases and N-acetylglucosaminidases in flies (Cattaneo et al, 1997(Cattaneo et al, , 2002Pasini et al, 1999;Perotti et al, 2001;Intra et al, 2006Intra et al, , 2009Intra et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%